Resilience Concepts and Planning Realities: How Quy Nhon Is Becoming a Resilient City by Integrating Climate Change Adaptation into Master Plans? - Ghimire, Jiwnath; Vu, Kim Chi; Thuy, Hang Nguyen Thi (Springer, 2018)
Resilience is a new concept in urban planning. Coming from ecology, resilience is continuously evolving in planning. Among several branches, the socio-ecological resilience is mostly emphasized. Measurement methods of resilience are also diverse. Quy Nhon is one of the major cities in South Central Coast of Vietnam with an area of 286 square kilometers and more than 287 thousand people. It is diverse in terms of ecology, land use and economy. Being at the South Central Coast, it faces typhoons and flooding events every year. With the El Nino and La Nina cycles, it also gets extremes temperature and cyclical events of drought. Quy Nhon’s case is an example of how cities build resilience to current and future disasters. As any other city of Vietnam, it follows standard Master Plan approach to guide its growth and to mainstream climate change adaptation and disaster risk reduction. But there is no systematic assessment of how this approach is leveraging existing urban planning mechanisms of the city and how the Master Plans are considering climate change and other disasters. This paper tries to address these questions. Two different methods will be used: (1) qualitative review of Quy Nhon Master Plans (2015 and 2004) from the perspective of climate change adaptation, (2) Interview with 29 government officials and leaders on their efforts on adaptation measures in the course of land use planning in the city. The major finding is that the level of awareness about climate change impacts is high among government officials and in Master Plan of 2015, assessment of impacts is moderate and actions to address those impacts are limited. Continuous incentives and supports can play a pivotal role to improve assessment and action on climate change impacts in the city.
Keywords: Stadtplanung; Resilienz; Masterplan; Implementierung; Klimawandel; Klimaanpassung; Ökologischer Stadtumbau; Fallstudie